Facile synthesis of nanorized zinc oxide by electrochemical method - Musthofa, M.; Razali, N. A. M.; Hairon, N. H.; Jalil, A. A.; Trihwayono, S. (2008)
Nanosized highly reactive zinc oxide (EGZnO/Naph) was readily synthesized by electrolysis of a N,Ndimethylformamide (DMF) solution containing naphthalene as a mediator followed by calcination at 823 K. XRD results showed that the product is high purity of zinc oxide. The particles size of EGZnO/Naph was confirmed by TEM which was varied between 10 to 30 nm. Nitrogen physisorption analysis showed that the surface area was 45.85 m2/g, which is 10 times larger than commercial zinc oxide. The FTIR spectrum shows the standard peak of zinc oxide at 450 cmâˆ’1.